Sociodemographic and sociocultural factors that influence blood donation in Perú: results of a national survey, 2022 - Almeyda Alcántara, Juan Antonio (2024)
Background: Sociodemographic and sociocultural factors influence blood donation in various countries, our objective of study was to determine what are the factors that influence blood donation in Peru. The study: An observational, crosssectional study was conducted in people between 18 and 60 years at the national level, the data were analyzed using SPSS v.20 Findings: The study sample was 739 people, 50.4% men; It was determined that there is good knowledge about blood donation with a percentage greater than 50% of questions answered correctly, likewise there is a positive attitude towards blood donation Conclusions: The sociocultural factors that influence blood donation is ignorance, 40% of the participants do not know the basic requirements to be a blood donor, another factor is the false belief. because they are taking medication, they cannot donate blood (47%).